THE IMPORTANCE OF INDIVIDUAL CHARACTERISTICS OF A PERSON IN THE PROCESS OF CHOOSING A PROFESSION - Akhmedov Rakhmatjon (Zeta Repository, 2023)
This article will highlight why is important for one to consider their personality when choosing a career. When choosing which career path to make, a lot of factors should come into consideration. One of them is whether you’ll be a good fit for the job because of your personality type. The main purpose of the study is to examine the relationship between personality traits and career choice and if these traits can affect the choice of major in the university/college. This study tries to concentrate on the way jobs are chosen and the impact of personality traits on this process from the connection between how students seen their personality and the various choices they prefer. Everyone possesses unique characteristics that differentiate them from others. These characteristics play a part in determining the success one is to have in a job.